ANALISIS PELAKSANAAN PRAKTIKUM ILMU PENGETAHUAN ALAM (IPA) BIOLOGI KELAS VIII DI SMP NEGERI 3 TAKALAR - Muhammad Riswan Ramli; Yusmar Yusuf; Ningsi Saibi; Nursia Nursia; Aswal Aswal (Biopedagogia, 2022)
This research is a descriptive study that aims to determine the level of implementation of Science biology lab VIII grade in SMP Negeri 3 Takalar. This sample is a class VIIIA to VIIIB SMP Negeri 3 Takalar taken randomly from each class to achieve the overall sample size of 80 students. Data retrieval is done by using a questionnaire aimed to determine the level of practical implementation, the questionnaire for barriers lab, and the fit between purpose laboratorioum with lab conducted. Data were analyzed using descriptive statistics in the form of percentage and average. Any number of questionnaires were given to respondents were scored practical implementation of the unit so that the percentage of the n obtained from the number of students who answered "never executed" the n unit divided by the total sample of students multiplied by 100%.        The result showed an average percentage of 43.74% for lab implementation. The percentage is quite low if the lab work is planned implemented in whole or 100% done. The factors that caused to the low percentage of lab implementation, namely the lack of facilities and infrastructure support, availability of equipment and lab materials, the lack of competence of teachers in guiding students to do lab work, lack of guidance lab implementation that can be used by students to undertake a lab, the allocation of time is not sufficient to carry out lab activities. Compliance levels with the goal of lab implementation of each unit that has been done on the subjects of science biology VIII has an average percentage of 78.30%.Keywords: Biology, Lab Implementation, and Lab Barriers